The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1074/jbc.m010915200
|View full text |Cite
|
Sign up to set email alerts
|

A Soluble Transforming Growth Factor-β (TGF-β) Type I Receptor Mimics TGF-β Responses

Abstract: Transforming growth factor-␤ (TGF-␤

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…As expected, sT␤RII-B.Fc or sT␤RII.Fc alone significantly bound 125 I-TGF-␤1 in a dose-dependent manner, whereas there was no significant binding to 125 I-TGF-␤2. Also, sT␤RI.Fc by itself did not bind either 125 I-TGF␤1, as has previously been reported (35), or 125 I-TGF-␤2. Next we mixed sT␤RII-B.Fc or sT␤RII.Fc at 10 and 50 ng together with 100 ng of sT␤RI.Fc in the presence of 125 I-TGF-␤2.…”
Section: St␤rii-bfc and St␤riifc Require St␤rifc Protein For Bindisupporting
confidence: 74%
“…As expected, sT␤RII-B.Fc or sT␤RII.Fc alone significantly bound 125 I-TGF-␤1 in a dose-dependent manner, whereas there was no significant binding to 125 I-TGF-␤2. Also, sT␤RI.Fc by itself did not bind either 125 I-TGF␤1, as has previously been reported (35), or 125 I-TGF-␤2. Next we mixed sT␤RII-B.Fc or sT␤RII.Fc at 10 and 50 ng together with 100 ng of sT␤RI.Fc in the presence of 125 I-TGF-␤2.…”
Section: St␤rii-bfc and St␤riifc Require St␤rifc Protein For Bindisupporting
confidence: 74%
“…On the other hand, definitive conclusions based on these results are limited, since artificial dimerization of the receptor may well underlie much of the cooperativity observed. An additional compromising aspect of these preparations was their homogeneity, which was not demonstrated by del Re et al 33 and questionable for the receptor produced by Docagne and co-workers, 41 since multiple high molecular mass species, likely disulfide-linked oligomers, were apparent in non-reducing SDS/polyacrylamide gels. In addition, this preparation of receptor extracellular domain had TGFb agonist, not antagonist activity as expected.…”
Section: Discussionmentioning
confidence: 94%
“…3,10 TbRII, the high-affinity receptor for TGFbs 1 and 3, has been shown to bind wedge-like between the fingertips on the distal end of the ligand homodimer. 15 Little is known regarding the mechanism by which TbRI is cooperatively recruited into the heterotetrameric receptor signaling complex, although two reports, one by Docagne et al 41 and another by del Re et al, 33 have shown that artificially dimerized, Fc-chimeric TbRI-ED cooperatively binds TGFb isoforms and Fc-chimeric TbRII-ED. On the one hand, these results are significant, since they provide experimental support for models of receptor assembly based on either direct 15 or indirect 21 interactions.…”
Section: Discussionmentioning
confidence: 99%
“…After 12 hours of incubation, supernatants were collected and frozen at Ϫ70°C. Active TGF␤ was measured as described previously by using the mink lung epithelial cell bioassay (25).…”
Section: Methodsmentioning
confidence: 99%
“…To test the potential mechanism for the osteophyte suppression, we examined the effect of ALN on the local release of active TGF␤ (Figure 7). Levels of active TGF␤ were measured in 24-hour-conditioned media derived from cultures of tibia plateaus or patellas obtained from rats subjected to ACLT, using the mink lung epithelial cell proliferation assay (25). This bioassay measured a combination of all TGF␤ isoforms.…”
Section: Aln Blocking Of the Recruitment Of Trappositive Cells To Ostmentioning
confidence: 99%